Terapi Hortikultural Untuk Meningkatkan Harga Diri Pada Pasien ODGJ di Wilayah Kerja Puskesmas TilongKabila - Putri Ariani, Gusti Ayu; Djauhari, Nurdian (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2024)
Background: Mental health is one of the top four health problems in the world. Mental health problems are not directly considered disorders that cause death. These disorders can result in the inability of individuals to behave, which can disrupt groups and communities and hinder development because they are counterproductive. One of the nursing actions that can be given to patients with low self-esteem is horticultural therapy. Purpose: This case study aims to see the picture of the application of horticultural therapy to increase self-esteem in patients with low self-esteem in the Tilongkabila Health Center Work Area.Methods: This case study uses a descriptive method and the Rosenberg Self Esteem Scale measuring instrument with 2 subjects and is carried out for 5 days.Results: The results showed an increase in self-esteem in both subjects after being given horticultural therapy.Conclusion: Based on the results of this case study, it can be concluded that horticultural therapy of planting chilies can increase the self-esteem of patients with low self-esteem in the Tilong Kabila Health Center Work Area.Keywords: Horticultural Therapy, low self-esteem, mental patients